2019
DOI: 10.1002/dvdy.60
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in modeling tuberous sclerosis with human stem cell‐derived neurons and brain organoids

Abstract: Recent advances in human stem cell and genome engineering have enabled the generation of genetically defined human cellular models for brain disorders. These models can be established from a patient's own cells and can be genetically engineered to generate isogenic, controlled systems for mechanistic studies. Given the challenges of obtaining and working with primary human brain tissue, these models fill a critical gap in our understanding of normal and abnormal human brain development and provide an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 108 publications
1
23
0
Order By: Relevance
“…1). Consistent with results from 2D neuronal cultures, a strong bias towards an astroglial cell fate, altered cell morphology, and activation of mTORC1 signaling were observed in this model [30,42] (Table 1). Additionally, it was shown that mosaic biallelic inactivation during neural progenitor expansion is necessary for the formation of dysplastic cells and increased glia production in three-dimensional cortical spheroids [30].…”
Section: Three-dimensional Modelssupporting
confidence: 87%
“…1). Consistent with results from 2D neuronal cultures, a strong bias towards an astroglial cell fate, altered cell morphology, and activation of mTORC1 signaling were observed in this model [30,42] (Table 1). Additionally, it was shown that mosaic biallelic inactivation during neural progenitor expansion is necessary for the formation of dysplastic cells and increased glia production in three-dimensional cortical spheroids [30].…”
Section: Three-dimensional Modelssupporting
confidence: 87%
“…These mutations include ASD-associated CNVs such as 15q11q13 deletion (Angelman syndrome) [121] and duplication (Dup15q syndrome) [122], 22q11.2 deletion (DiGeorge syndrome) [123,124], 16p11.2 deletion and duplication [125], and 15q13.3 deletion [126], as well as single-gene mutations including SHANK3 [127][128][129][130], CHD8 [131,132], NRXN1 [133][134][135][136][137], NLGN4 [138], EHMT1 (Kleefstra syndrome) [139], PTCHD1-AS [140], UBE3A (Angelman's syndrome) [141], and CACNA1C (Timothy syndrome) [142] (summarized in Table 1). In this review, we will not discuss fragile X syndrome, Rett's syndrome, and tuberous sclerosis-related autism as they have all been extensively reviewed previously [148][149][150][151][152][153][154].…”
Section: Main Findings From Stem Cell Models Of Asd To Datementioning
confidence: 99%
“…Hyperactivation of the mTOR pathway has been implicated in the development of cortical tubers as mTORC1 has a well-established role in cell proliferation and cell fate choices [31]. However, molecular mechanisms of tuber formation are difficult to study in animal models as, so far, no animal model of TSC develops an equivalent to cortical tubers [13]. Early knockout of either TSC1 or TSC2 in rodents is lethal necessitating a conditional knockout of TSC1 or TSC2 in either neurons or astrocytes at later stages of neurodevelopment in animal models [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, research into mechanistic insights of seizure generation can be limited when using rodent models owing to significant differences in neuronal organization and brain development between rodents and humans [12]. Moreover, genetic epilepsy syndromes such as TSC are challenging to study in animal models, since pathogenic mechanisms likely originate from events during early neural development, a phase that differs profoundly between rodents and humans in terms of cell type diversity, proliferation zones, and timescales [13,14]. This translational barrier might be an important reason why mechanisms underlying human epileptogenesis are still not fully understood [15] and may, at least partly, explain why a preventative or disease-modifying antiepileptogenic therapy is not available in clinical practice, despite promising preclinical results [16].…”
Section: Introductionmentioning
confidence: 99%